2023
DOI: 10.37496/rbz5220220052
|View full text |Cite
|
Sign up to set email alerts
|

The economic value of sustainability of the integrated crop-livestock system in relation to conventional systems

Abstract: The objective of this study was to evaluate the potential of improving the economic value of integrated crop-livestock systems (ICLS) compared to conventional systems specialized in monoculture. The experimental area was 16.02 ha, divided into 18 paddocks of 0.89 ha each, organized in a randomized block design, with three replicates and six models of production systems: crop system [corn (Zea mays) grain production], livestock system (beef cattle under grazing conditions), and four ICLS, identified as: ICLS-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Adoption of integrated crop-livestock system (ICLS) reduces agricultural activity risk. Risk analysis research concluded that it was advantageous for ICLS products to be diversified [ 40 , 41 ]. Nevertheless, the system was more complicated because it called for the producer to possess a wider range of technical and commercial understanding of livestock- and agriculture-related activities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adoption of integrated crop-livestock system (ICLS) reduces agricultural activity risk. Risk analysis research concluded that it was advantageous for ICLS products to be diversified [ 40 , 41 ]. Nevertheless, the system was more complicated because it called for the producer to possess a wider range of technical and commercial understanding of livestock- and agriculture-related activities.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the system was more complicated because it called for the producer to possess a wider range of technical and commercial understanding of livestock- and agriculture-related activities. Furthermore, it was thought that ICLS was less susceptible to changes in market and operational variables [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations